Sistem Informasi Penjualan Online di Universitas Katolik Santo Thomas (Tokounika) Berbasis Web Menggunakan Metode Feature Driven Development - Harianja, Andy Paul; Talunohi, Iwada Grawilser (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2021)
The development of the field of information technology is very rapid, therefore many companies, industries, shops and other business entities are using information systems to increase their business. Online sales information systems are used to carry out business processes such as distribution, sales, purchasing, marketing of goods or services by using communication networks and the internet. Online sales information systems can help people who do not have a place or shop to carry out their business. Students in this case, especially at the Catholic University of Santo Thomas, are an opportunity to take advantage of this facility in carrying out their business, especially if they do not have a place or shop to carry out their business. For this reason, an online sales information system was built that can be accessed through the website.